Customer inertia marketing - Henderson, Conor M.; Steinhoff, Lena; Harmeling, Colleen M.; Palmatier, Robert W. (Journal of the Academy of Marketing Science)
Keywords: Marketing; Economics and Econometrics; Business and International Management

Toward a comprehensive framework of value proposition development: From strategy to implementation - Payne, Adrian; Frow, Pennie; Steinhoff, Lena; Eggert, Andreas (Industrial Marketing Management)
Keywords: Marketing

Data Privacy in Retail - Martin, Kelly D.; Kim, Jisu J.; Palmatier, Robert W.; Steinhoff, Lena; Stewart, David W.; Walker, Beth A.; Wang, Yonggui; Weaven, Scott K. (Journal of Retailing)
Keywords: Marketing

Understanding and managing customer value propositions: Introduction to the special issue - Eggert, Andreas; Frow, Pennie; Payne, Adrian; Steinhoff, Lena (Industrial Marketing Management)
Keywords: Marketing

Commentary: Opportunities and challenges of technology in relationship marketing - Steinhoff, Lena; Palmatier, Robert W. (Australasian Marketing Journal)
Keywords: Marketing; Economics and Econometrics

 Zeitschrift für Romanische Sprachen und ihre Didaktik

Experimental and Theoretical Study on the Role of Monomeric vs Dimeric Rhodium Oxazolidinone Norbornadiene Complexes in Catalytic Asymmetric 1,2- and 1,4-Additions - Kirchhof, Manuel; Gugeler, Katrin; Fischer, Felix Richard; Nowakowski, Michal; Bauer, Alina; Alvarez-Barcia, Sonia; Abitaev, Karina; Schnierle, Marc; Qawasmi, Yaseen; Frey, Wolfgang; Baro, Angelika; Estes, Deven P.; et al. (Organometallics)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry

Charge Distribution in Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes: A Combined X-ray, XAS, XES, DFT, Mössbauer, and Catalysis Approach - Benedikter, Mathis; Musso, Janis; Kesharwani, Manoj K.; Sterz, K. Leonard; Elser, Iris; Ziegler, Felix; Fischer, Felix; Plietker, Bernd; Frey, Wolfgang; Kästner, Johannes; Winkler, Mario; van Slageren, Joris; et al. (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Electronic Structure of the Hieber Anion [Fe(CO)3(NO)]− Revisited by X-ray Emission and Absorption Spectroscopy - Burkhardt, Lukas; Vukadinovic, Yannik; Nowakowski, Michał; Kalinko, Aleksandr; Rudolph, Julian; Carlsson, Per-Anders; Jacob, Christoph R.; Bauer, Matthias (Inorganic Chemistry)
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Stereoselective Chromium‐Catalyzed Semi‐Hydrogenation of Alkynes - Gregori, Bernhard J.; Nowakowski, Michal; Schoch, Anke; Pöllath, Simon; Zweck, Josef; Bauer, Matthias; Jacobi von Wangelin, Axel (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

The role of caregivers in keeping a child-robot interaction going. - Rohlfing, Katharina; Grimminger, Angela; Wrede, Britta (International perspectives on digital media and early literacy: The impact of digital devices on learning, language acquisition and social interaction.)

Ethical Considerations of Applying Robots in Kindergarten Settings: Towards an Approach from a Macroperspective - Tolksdorf, Nils F.; Siebert, Scarlet; Zorn, Isabel; Horwath, Ilona; Rohlfing, Katharina J. (International Journal of Social Robotics)
In child–robot interaction (cHRI) research, many studies pursue the goal to develop interactive systems that can be applied in everyday settings. For early education, increasingly, the setting of a kindergarten is targeted. However, when cHRI and research are brought into a kindergarten, a range of ethical and related procedural aspects have to be considered and dealt with.While ethical models elaborated within other human–robot interaction settings, e.g., assisted living contexts, can provide some important indicators for relevant issues, we argue that it is important to start developing a systematic approach to identify and tackle those ethical issues which rise with cHRI in kindergarten settings on a more global level and address the impact of the technology from a macroperspective beyond the effects on the individual. Based on our experience in conducting studies with children in general and pedagogical considerations on the role of the institution of kindergarten in specific, in this paper,we enfold some relevant aspects that have barely been addressed in an explicit way in current cHRI research. Four areas are analyzed and key ethical issues are identified in each area: (1) the institutional setting of a kindergarten, (2) children as a vulnerable group, (3) the caregivers’ role, and (4) pedagogical concepts. With our considerations, we aim at (i) broadening the methodology of the current studies within the area of cHRI, (ii) revalidate it based on our comprehensive empirical experience with research in kindergarten settings, both laboratory and real-world contexts, and (iii) provide a framework for the development of a more systematic approach to address the ethical issues in cHRI research within kindergarten settings.
Keywords: Robot ethics · Kindergarten settings · Child–robot interaction · Early childhood education

Wie meinst du das? - Begriffserwerb im Religionsunterricht - Kohlmeyer, Theresa; Reis, Oliver; Viertel, Franziska; Rohlfing, Katharina (Theo Web)

International Perspectives on Digital Media and Early Literacy

Spatially single mode photon pair source at 800 nm in periodically poled Rubidium exchanged KTP waveguides - Eigner, Christof; Padberg, Laura; Santandrea, Matteo; Herrmann, Harald; Brecht, Benjamin; Silberhorn, Christine (Optics Express)

Integrated Communication System: Gesture and language acquisition in typically developing children and children with LD and DLD - Lüke, Carina; Ritterfeld, Ute; Grimminger, Angela; Rohlfing, Katharina; Liszkowski, Ulf (Frontiers in Psychology 11)

Sexuelle Vielfalt in der Religionspädagogik - Uppenkamp, Vera (Inklusive Religionspädagogik der Vielfalt. Konzeptionelle Grundlagen und didaktische Konkretionen)

Armut und Reichtum - Uppenkamp, Vera (Inklusive Religionspädagogik der Vielfalt. Konzeptionelle Grundlagen und didaktische Konkretionen)

Hören – Sprechen – Lesen – Schreiben. Basale Sprachfähigkeiten. - Topalović, Elvira; Uhl, Benjamin

Hören – Sprechen – Lesen – Schreiben. Basale Sprachfähigkeiten. - Topalović, Elvira; Uhl, Benjamin